Conventional Two-Stage Hepatectomy or Associating Liver Partitioning and Portal Vein Ligation for Staged Hepatectomy for Colorectal Liver Metastases? A Systematic Review and Meta-Analysis - Zhang, Liang; Yang, Zhentao; Zhang, Shiyu; Wang, Wenchao; Zheng, Shusen (Frontiers in Oncology, 2020)
Background: Pushing the surgical limits for initially unresectable colorectal liver metastases (CRLM) are two approaches for sequential liver resection: two-stage hepatectomy (TSH) and associating liver partitioning and portal vein ligation for staged hepatectomy (ALPPS). However, the role of each treatment modality remains ill-defined. The present meta-analysis was designed to compare the safety, efficacy and oncological benefits between ALPPS and TSH in the management of advanced CRLM. Methods: A systematic literature search was conducted from online databases through to February 2020. Single-arm synthesis and cumulative meta-analysis were performed. Results: Eight studies were included, providing a total of 409 subjects for analysis (ALPPS: N=161; TSH: N=248). The completions of the second stage of the hepatectomy [98% vs 78%, odds ratio (OR) 5.75, p<0.001] and R0 resection (66% vs 37%; OR 4.68; p<0.001) were more frequent in patients receiving ALPPS than in those receiving TSH, and the waiting interval was dramatically shortened in ALPPS (11.6 vs 45.7 days, weighted mean difference = -35.3 days, p<0.001). Nevertheless, the rate of minor complications was significantly higher in ALPPS (59% vs 18%, OR 6.5, p<0.001) than in TSH. The two treatments were similar in 90-day mortality (7% vs 5%, p=0.43), major complications (29% vs 22%, p=0.08), posthepatectomy liver failure (PHLF; 9% vs 9%, p=0.3), biliary leakage (11% vs 14%, p=0.86), length of hospital stay (27.95 vs 26.88 days, p=0.8), 1-year overall survival (79% vs 84%, p=0.61), 1-year recurrence (49% vs 39%, p=0.32) and 1-year disease-free survival (34% vs 39%, p=0.66). Cumulative meta-analyses indicated chronological stability for the pooled effect sizes of resection rate, 90-day mortality, major complications and PHLF. Conclusions: Compared with TSH, ALPPS for advanced CRLM resulted in superior surgical efficacy with comparable perioperative mortality rate and short-term oncological outcomes, while this was at the cost of increased perioperative minor complications.